2017
DOI: 10.1016/j.jvs.2016.07.105
|View full text |Cite
|
Sign up to set email alerts
|

A novel chronic advanced stage abdominal aortic aneurysm murine model

Abstract: Objective The purpose of this study was to establish a reliable, chronic model of abdominal aortic aneurysm (AAA). Materials and methods 120 eight-week old C56BL/6 male mice were equally divided into three groups: 1) BAPN Group: 0.2% 3-aminopropionitrile fumarate salt (BAPN) drinking water was provided to mice two days before surgery until the end of study. Sham aneurysm induction surgery was performed using 5 μl of heat de-activated elastase. 2) Elastase Group: Mice were given regular drinking water without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(175 citation statements)
references
References 22 publications
7
143
1
1
Order By: Relevance
“…44 Recent addition of BAPN (inhibitor of lysly oxidase) to the drinking water of the elastase aneurysm model does result in spontaneous ILT formation, similar to humans. 45 Furthermore, although human aneurysms have an abundance of neutrophil infiltration (;70% neutrophil contribution), most animal models are characterized by high monocyte/macrophage and lymphocyte infiltration (;10% neutrophil contribution). 46,47 However, although it is difficult to model a complex and heterogenous pathophysiology in animal models, these models are still useful to define mechanisms and pathways that may affect the human condition and provide complementary studies to test targeted therapeutics.…”
Section: Nonocclusive Trilayered Iltmentioning
confidence: 99%
“…44 Recent addition of BAPN (inhibitor of lysly oxidase) to the drinking water of the elastase aneurysm model does result in spontaneous ILT formation, similar to humans. 45 Furthermore, although human aneurysms have an abundance of neutrophil infiltration (;70% neutrophil contribution), most animal models are characterized by high monocyte/macrophage and lymphocyte infiltration (;10% neutrophil contribution). 46,47 However, although it is difficult to model a complex and heterogenous pathophysiology in animal models, these models are still useful to define mechanisms and pathways that may affect the human condition and provide complementary studies to test targeted therapeutics.…”
Section: Nonocclusive Trilayered Iltmentioning
confidence: 99%
“…In combination with AngII, a blood pressure elevator, AD and aneurysms are induced in these mice 22 . Research has indicated that, compared to other mouse models, the BAPN + AngII mice are more prone to develop medial ruptures 25 27 . This observation and the fact that the BAPN + AngII infusion leads to aneurysm- and dissection-like symptoms 22 , 25 , 26 may explain the recent surge in research papers that use the BAPN mice and rats as a model for aneurysms 25 , 27 , dissections 22 , or both 23 .…”
Section: Introductionmentioning
confidence: 96%
“…In another study, DPP4 inhibition decreased the formation of aneurysm, elastin degradation, expression of MMP2 and -9, gelatinolytic activity, aortic apoptotic signal and macrophage infiltration in a mouse model, with similar results shown for GLP-1 [14]. All animal model have different limitations and studying DPP4 inhibition in other recently developed models could yield additional insight [45,46]. Further, DPP4 is known to interact with fibronectin and collagen [47,48], and has been shown to be involved in a complex with fibroblast activation protein α that locally degraded ECM thus enabling endothelial cell invasion and migration [49].…”
Section: Discussionmentioning
confidence: 52%